Dynamic changes in transcriptome during orthodontic tooth movement - Liu, Jia; Chen, Po‐Jung; Mehta, Shivam; Dutra, Eliane H.; Yadav, Sumit (Orthodontics & craniofacial research, 2023)
Objectives The objective of this study was to determine global changes in gene expression with next generation sequencing (NGS) in order to assess the biological effects of orthodontic tooth movement (OTM) on alveolar bone in a rat model. Materials and Methods Thirty‐five Wistar rats (age 14 weeks) were used in the study. The OTM was performed using closed coil Nickel–Titanium spring to apply a mesial force on maxillary first molars of 8–10 g. Three hours, 1, 3, 7 and 14 days after the placement of the appliance, rats were killed at each time point respectively. The alveolar bone, around left maxillary first molar, were excised on compression side. The samples were immediately frozen in liquid nitrogen for subsequent RNA extraction. Total RNA samples were prepared for mRNA sequencing using the Illumina kit. RNA‐Seq reads were aligned to the rat genomes using the STAR Aligner and bioinformatic analysis was performed. Results A total of 18 192 genes were determined. Day 1 has the highest number of differentially expressed genes (DEGs) observed with more upregulated than downregulated genes. A total of 2719 DEGs were identified to use as input for the algorithm. Six distinct clusters of temporal patterns were observed representing proteins that were differentially regulated indicating different expression kinetics. Principal component analysis (PCA) showed distinct clustering by time points and days 3, 7 and 14 share similar gene expression pattern. Conclusions Distinct gene expression pattern was observed at different time points studied. Hypoxia, inflammation and bone remodelling pathways are major mechanisms behind OTM.